Atmospheric physics 5: Barometric formula

Assume that the atmosphere has a homogeneous temperature T ( z ) = T 0 = const T(z) = T_0 = \text{const} (isothermal atmosphere), regardless of the altitude z z . In addition, the air is treated as an ideal gas.

Which mathematical form then has the barometric formula for the pressure P ( z ) ? P(z)?

Here, P 0 P_0 denotes the pressure at sea level, and H H the scale height.


Hints: Use the hydrostatic equation and the general gas equation d P d z = g ρ and P = R ρ T \frac{dP}{dz} = - g \rho \quad \text{ and } \quad P = R^\ast \rho T from the previous parts to derive a differential equation for the pressure P = P ( z ) P = P(z) . Which of these functions solves this differential equation? What results for the scale height H ? H?

P ( z ) = P 0 [ 1 z H ] α P(z) = P_0 \left[1 - \dfrac{z}{H} \right]^{\alpha} P ( z ) = P 0 exp ( z H ) P(z) = P_0 \exp\left(- \dfrac{z}{H} \right) P ( z ) = P 0 H z + H P(z) = P_0 \dfrac{H}{z + H}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

By combining the hydrostatic equation with the general gas equation we can eliminate the density ρ \rho P = ρ R T M ρ = M R T P d P d z = ρ g = M g R T P \begin{aligned} & & P &= \rho \frac{RT}{M} \\ \Rightarrow & & \rho &= \frac{M}{RT} P \\ \Rightarrow & & \frac{dP}{dz} &= -\rho g = -\frac{M g}{R T} P \end{aligned} Since the temperature is a constant T = T 0 T = T_0 , the pressure P P is the only unknown, which depends on the alititude z z . Thus, we haven a differential equation for the pressure, which can be solved by separation of variables: d P d z = M g R T P d P P = M g R T d z P 0 P ( z ) d P P = M g R T 0 z d z log P ( z ) P 0 = M g R T z P ( z ) = P 0 exp [ M g R T z ] \begin{aligned} & & \frac{dP}{dz} &= -\frac{M g}{R T} P \\ \Rightarrow & & \frac{dP}{P} &= -\frac{M g}{R T} dz \\ \Rightarrow & & \int_{P_0}^{P(z)} \frac{dP}{P} &= -\frac{M g}{R T} \int_{0}^{z} dz \\ \Rightarrow & & \log \frac{P(z)}{P_0} &= -\frac{M g}{R T} z \\ \Rightarrow & & P(z) &= P_0 \exp \left[ -\frac{M g}{R T} z \right] \end{aligned} Thus, the solution is an exponential function P = P 0 e z / H P = P_0 e^{-z/H} with the scale height H = R T / M g H = RT/M g .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...